بحوث التسويق والتنمية السياحية عبر منصة المجلات العلمية الجزائرية: مراجعة للمواضيع وآفاقها Researches about Tourism Marketing through ASJP: Review of Topics and Future Perspectives - بن شوري عيسى (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
دى تذبذب الطلب السياحي بسب الأزمات المختلفة إلى زيادة حدة المنافسة بين الوجهات لجذب السياح؛ فاحتاج القائمون عليها إلى استراتيجيات التسويق لاكتساب ميزات تنافسية؛ فارتأينا مراجعة بحوث ومواضيع التسويق السياحي بالتحديد المبدئي لـ:213 مقالًا حول مواضيع التسويق السياحي (ككلمة مفتاحية) والتي نُشرت في قاعدة بيانات منصة المجلات العلمية الجزائرية خلال (يناير2012 إلى جوان2022)، وتم فحص هذه المقالات وتصنيفها وفقًا لمعايير مثل: موضوعات البحث، البيانات الببليوغرافية، طرق الدراسة وجمع البيانات، تقنيات التحليل، الأطر النظرية وأماكن الدراسة؛ ووجدنا أن معظم المقالات تستند إلى دراسات المفاهيم ودراسات الحالة والدراسات الكيفية، ويَظهر التسويق السياحي (بتنوع موضوعاته) كموضوعِ بحثٍ رئيس في جميع الدراسات؛ وحاولنا من خلال هاته المقالة تقديم طرقٍ أفضل للبحث في المستقبل بتحديد الفجوات في البحوث الموجودة. Abstract: The instability of tourist demand due to various crises has increased competition between destinations to attract tourists; Responsible of such destinations needed marketing strategies to gain a competitive advantage. We propose a review of Tourism Marketing researches, thus 213 articles published in the ASJP from January 2012 to June 2022 were initially selected on tourism marketing. These articles were analyzed and classified according to: research topics, bibliographic data, methods and data collection, analysis techniques, theoretical frameworks and study places. Our results show that most of the articles are based on concept, case and qualitative studies. Tourism Marketing appears as a major research topic in all studies(as a keyword). We have tried here to provide better ways for future researches by identifying the main lack in reviewed research.